Implementasi Penggelolaan Penerangan Jalan Umum Kecamatan Jabon Kabupaten Sidoarjo - Cindy Dwi Maulidiya; Indah Prabawati; Tjitjik Rahaju; M. Noer Falaq Al Amin (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Street Lighting (PJU) is a public service that plays a vital role in supporting the safety, security, and comfort of road users, especially at night. Street lighting management in Sidoarjo Regency is implemented based on Sidoarjo Regent Regulation Number 58 of 2022. However, in Jabon District, problems are still found in the form of damaged and non-functioning street lights. This study aims to describe and analyze the implementation of street lighting management in Jabon District, Sidoarjo Regency. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The analysis was carried out using the George C. Edward III policy implementation model which includes indicators of communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the implementation of street lighting management in Jabon District has generally run well. In the communication indicator, implementation is considered quite effective through coordination meetings, although communication with the community is still not optimal so that participation in reporting street lighting problems is relatively low. The resource indicator is supported by the availability of competent human resources, clear authority, and adequate facilities. In the disposition indicator, policy implementers demonstrate high commitment and responsibility. Meanwhile, a bureaucratic structure supported by standard operating procedures (SOPs) and a clear division of authority also contributes to the smooth management of street lighting. Suggestions include increasing direct outreach to the community at the village level and expanding information on street lighting complaint channels to ensure wider access.